O “nós” e o “outro” nas relações de trabalho de venezuelanos e haitianos em Boa Vista - Roraima - Level, Beatriz Patrícia de Lima (2020)
This study aimed to understand the working relationships of Venezuelan and Haitian migrants, in the face of the adversities that these people face simply because they are migrants. Our purpose, then, was to analyze the working conditions of these people, identifying whether racism / xenophobia was a factor that influenced their working conditions and consequently the relationships they established in the city of Boa Vista, capital of the state of Roraima. The research was justified by the increase and intensification of international migration to the municipality of Boa Vista and in view of this, the need to understand this migratory process, both for migrant subjects and for the society of Boa Vista. The methodology used was qualitative and the selection of respondents was intentional of a qualitative character. Using the semi-structured interview technique, a total of 25 people was interviewed. We also used the technique of participant observation and field-theme. The method of analysis of the interviews was the Textual Discursive Analysis - ATD. Throughout the research, we came to the conclusion that the condition of the Venezuelan and Haitian migrants in the city is precarious; the jobs they do are mostly in the informal sector; and that these migrants, in most cases, suffer from infrapolytic racism / xenophobia, which directly affects all the relationships that they establish in the city, including labor relations, the focus of this study.